(untitled) (Al-Qamar, 2022)
Islamic scholars are the capital of any country and they play an important role in the religious and political development of the country. Due to the Islamic scholars we learn religious and worldly sciences. The status of Islamic scholars is very important in the eyes of God and His messenger. God has said that "An educated person is much better than an uneducated person". If we look at the history of the sub-continent, we will know that the Islamic scholars faced severe hardships for the development of religion. When the British colonialism started in the Indian subcontinent, the power of Islam weakened. Religions characteristics were declining. Rituals innovations and myths will spread, and in the Muslim Ummah there was a state of anxiety. On this occasion scholars came forward and they managed the plight of the Muslims. Just as the Islamic scholars of Dera Ismail Khan have been very important in the religious and political field of the country since the beginning. Due to which their services cannot be forgotten.